Architectonics of the Analysis and Information System "Anti-Crisis" - Kuklin, Aleksandr Anatolyevich; Okhotnikov, Sergey Aleksandrovich; Korshunov, Lev Aleksandrovich (Economy of Regions, 2016)
The article presents the flowchart of the and analysis and information system “Anti-crisis” intended for the integrated assessment of the parameters of the economic security of the constituent entities of the Russian Federation. This system takes into account the risks, threats and their forecasting. The scheme reflects the interaction of separate program modules. The integration of modules with the unified database management system is described: access to the database, automatic backup and recovery of databases in real time, data transmission through an open channel with the use of modern encryption-decryption algorithm. The main units of the system are allocated: a diagnostic block of the economic security condition, block of the well-being of an individual and the territory of residence, block of extremism, correlation block, block of modelling and forecasting the security of the entities of the Russian Federation. Within the block of the modelling, the main generalized mathematical model based on the system of the nonlinear differential equations and created for the purpose to take into account the correction coefficients, as well as all types of interaction of indicators, is given. The main types of optimization problems of the interaction of indicators by using the generalized model, are compiled. On the basis of the developed optimization problems, the forecasting from 2016 to 2020 is made.